Institutions’ quality and economic performance in the EU: insights from a cluster analysis - Olga Lavrinenko; Svetlana Ignatjeva; Alina Danileviča; Vera Komarova; Stanislav Vaisla (Entrepreneurship and Sustainability Issues, 2025)
The article examines the complex relationship between institutions and economic performance in the EU. Institutions’ quality will be measured by corruption (measured by the Corruption Perceptions Index) and so-called “state fragility” (measured by the Fragile States Index); economic performance will be measured by GDP per capita in PPP. Using hierarchical cluster analysis, the study classifies the EU countries into two groups: (1) countries with high corruption, low quality of public institutions and low economic performance, and (2) countries with low corruption, strong public institutions and high economic performance. This method reveals differences in the impact of corruption and fragile states on economic performance, making the analysis more comprehensive than linear regression models. The study results show that in countries with high corruption and low quality of public institutions, economic performance is significantly lower, and corruption has a more significant negative impact on the economy. At the same time, in the more developed countries, where corruption is low, economic performance is related to the Fragile States Index. These differences underscore that in less developed countries, the fight against corruption should be a key priority, while in more developed countries, the focus should be on strengthening public institutions to sustain high economic performance. The results of the study have important foresight conclusions. In countries with high corruption and low level of quality of public institutions, without decisive measures to address them, economic performance could be expected to continue to decrease, leading to greater economic and social imbalances. For countries with high economic performance and strong public institutions, the emphasis on institution-building will contribute to more sustainable economic performance in the long term. It is expected that countries that effectively combat corruption and strengthen their public institutions will be able to improve economic performance, attract more investment and increase global competitiveness. The study provides a new perspective on the relationship between corruption, fragile states and economic performance, for the first time classifying the EU countries on the basis of these indicators. The results of the study point to the need to develop adapted policies aimed at strengthening public institutions and reducing corruption, which are important for sustaining and increasing economic performance in different groups of the EU countries.